A VALUE OF BODY CONDITION SCORE (BCS), SERVICE PER CONCEPTION (S/C) AND CALVING INTERVAL (CI) ONGOLE CROSSBREEDS IN DELI TUA DISTRICT - Jefri Batubara; Sukma Aditya Sitepu; Andhika Putra (Sean Institute, 2022)
This study aims to determine the relationship between Body Condition Score and Service per Conception and Calving Interval of Ongole Crossbreeds in Deli Tua District. The material used was 75 Ongole Crossbreed cows. The method used is a case study, data collection is carried out primary and secondary. The variables observed were Body Condition Score (BCS), Service per Conception (S/C), Calving Interval (CI). The results showed that the average Body Condition Score (BCS) for PO cattle was 2, the S/C value was 1.9 and the Calving Interval was 14-15 months